DNA topoisomerases methods and protocols (Methods in molecular biology, 2012)
"Due to their importance to cell biology, DNA topology-altering enzymes, collectively DNA topoisomerases and gyrases, have been studied thoroughly from a biochemical perspective, yet the expansion of research at the molecular and cellular levels continues to show a great deal of promise. In DNA Topoisomerases: Methods and Protocols, experts in the field present a compendium of protocols that extends into the new areas of research that have been recently uncovered in order to elucidate the methodology needed to study topoisomerases in the molecular and cellular context. The volume examines subjects such as the analysis of DNA topologies and the interaction of topoisomerases with DNA as tools to measure topoisomerase functions, the binding of topoisomerases to specific sites in the genomes of eukaryotes, including origins of DNA replication, as well as exploration of perturbed topoisomerase function. As a volume in the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, laboratory protocols, and notes on trouble-shooting and avoiding known pitfalls." "Cutting-edge and easy-to-use, DNA Topoisomerases: Methods and Protocols provides key content which reflects an expanded understanding of the functions of these essential enzymes in the hope of inspiring researchers to further important discoveries in this dynamic field."--BOOK JACKET.